Day-Ahead Coordinated Low Carbon Robust Scheduling of Hydro-Electricity-Natural Gas System Considering Power-to-Gas to Accommodate Excessive Hydro Generation - Hongyuan XU; Taicong LONG; Qidao ZHAO; Pai LI; Lu NAN; Qi ZHANG; Yuhang CHEN; Jing TAN (Zhongguo dianli)
Aiming at the surplus water problem caused by insufficient regulation capacity of power system and uncertainty on the load side, a multi-energy coordinated low-carbon robust scheduling model of hydro-electricity-natural gas system was proposed and solved in this paper. The nonlinear constraint in the proposed model is transformed into a mixed-integer linear model based on piecewise linearization method and Taylor series expansion method. For the uncertain parameters in the model, the column and constraint generation method are used to further transform it into a master-subproblem framework, consequently solved by GUROBI solver. Numerical results of an improved 6-bus electricity/7-node gas system show that the proposed model can make full use of the complementary characteristics of different energy systems to improve the regulation capacity of the power system and promote the consumption of hydro power, as well as reduce the operation cost and achieve low-carbon operation of power system.